PERAN ETIKA BISNIS ISLAM DALAM MEMBANGUN KEPERCAYAAN KONSUMEN: SEBUAH STUDI KASUS UMKM DI TANGGERANG SELATAN - Abdullah Pelu, Muhammad Fariz (Media Riset Bisnis Ekonomi Sains dan Terapan, 2025)
Islamic business ethics is a fundamental foundation in building customer trust, particularly in the Micro, Small, and Medium Enterprises (MSMEs) sector. This study aims to analyze the role of Islamic business ethics in fostering customer trust, focusing on MSMEs in Cirendeu, South Tangerang. This qualitative research employs a literature review methodology, with data collected from various sources such as books and scientific journals. The findings reveal that values such as honesty (ṣidq), justice (ʿadl), responsibility (amānah), and transparency play key roles in establishing harmonious relationships between business owners and customers. The implementation of Islamic business ethics not only enhances customer loyalty but also positively impacts local communities through economic empowerment and improved welfare. This study also supports Stakeholder Theory, which emphasizes the importance of meeting the expectations of all stakeholders. Hence, the application of Islamic business ethics values provides relevant and practical solutions to modern business challenges, particularly in the MSME sector. The study recommends specialized training and mentoring for MSME actors to enhance their understanding and implementation of Islamic business ethics principles, as well as further research that encompasses broader regions and business sectors, including digitalization contexts.Keywords : Islamic Business Ethics, Customer Trust, MSMEs, Honesty, Justice, Responsibility.